(untitled) (Modern education and development, 2025)
The significant advancement of globalisation, which has affected every sphere of activity, has increased the importance of intercultural competence in training future specialists. However, current research results indicate the insufficient effectiveness of this skill among university graduates, prompting scholars to search for new pedagogical methods to foster its development. This study aimed to identify the main stages involved in the formation of intercultural competence and to examine the role of media education in this process. To accomplish this, the study employed several methods, including a literature review, an analysis of competence development stages, an experimental study with subsequent statistical analysis and comparison of test outcomes, data visualisation, and synthesis of conclusions. The research revealed five stages of competence formation: denial, defence, acceptance, adaptation, and integration. The study confirmed the effectiveness of media education - especially through video lessons and video presentations - in developing intercultural skills. A strong positive correlation was identified between the number of video presentations created by students and their positive test responses. Consequently, media education has a beneficial impact on the formation of intercultural competence and, due to its specific features, can be effectively integrated into the educational process.